Marketing Strategy Formulating Mekarbuana Village Tourism Kec. Tegalwaru Regency. Karawang - Sumarni, Neni (Media Wisata, 2023)
Mekarbuana Village, one of the villages in Karawang, has enormous tourism potential. This study aimed to determine and determine the tourism marketing strategy for Mekarbuana village. This study uses descriptive qualitative with SWOT analysis techniques through IFAS and EFAS analysis based on economic, socio-cultural, environmental and village government instruments. Data collection is based on literature study, observation and in-depth interviews with village tourism managers. Based on the results of marketing strategy research, potential development needs to be done. Possible development can be carried out through the potential possessed by the village, one of which is natural potential, making tour packages, using social media as a means of promotion, marketing facilities, improving tourism facilities, and involving the community in developing their MSMEs to encourage innovation through the use of additional tourism such as procurement of homestays, ecotourism-based coffee village tours.